La estimulación temprana y su incidencia dentro del desarrollo cognitivo de los niños y niñas de la sección de maternal del centro de desarrollo infantil Colibrí de la provincia de Cotopaxi, cantón Latacunga, parroquia San Buenaventura en el periodo 2014 - 2015” - Rodríguez Herrera, Alexandra Jeaneth (2015)
This research was conducted with the purpose to known the whole educational community importance of early stimulation on children with cognitive development 2 and 3 years old and their recognition the process, which promotes the development of the child, according to size, quality and relevance of providing favorable stimuli and social impact on everyone involved in this environment in order to change the traditional process of principles and education of children, and that through this research it has been shown that the lack of parental time has been an influential factor in the Physicosocialaffective development of children with this has been tried not only to achieve the simple knowledge but to promote and encourage their skills, abilities and generating potential individuals participate in society for this reason it is essential to early stimulation as a tool for cognitive development of children at Nursery section C.D.I. "Colibrí".